2020
DOI: 10.6061/clinics/2020/e1989
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Endoscopic Procedures: A Routine Protocol from a Quaternary University Referral Center Exclusively for Coronavirus Disease 2019 Patients

Abstract: The present coronavirus disease (COVID-19) pandemic has ushered in an unprecedented era of quality control that has necessitated advanced safety precautions and the need to ensure the adequate protection of healthcare professionals (HCPs). Endoscopy units, endoscopists, and other HCP may be at a significant risk for transmission of the virus. Given the immense burden on the healthcare system and surge in the number of patients with COVID-19, well-designed protocols and recommendations are needed. We aimed to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…Out the outset of the pandemic, this quaternary university referral center instituted a protocol to exclusively care for COVID-19 patients. This hospital and institution is comprised of the largest public hospital in South America ( 11 ). The hospital is designed to care for patients presenting with moderate and severe disease and receives patient referrals following local government protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out the outset of the pandemic, this quaternary university referral center instituted a protocol to exclusively care for COVID-19 patients. This hospital and institution is comprised of the largest public hospital in South America ( 11 ). The hospital is designed to care for patients presenting with moderate and severe disease and receives patient referrals following local government protocol.…”
Section: Methodsmentioning
confidence: 99%
“…As disease prevalence, presenting symptoms, and outcomes have varied from reports in China to those in the United States and Europe, examination of COVID-19 specific characteristics is highly relevant for the population of Brazil and South America. Therefore, the primary aim of this study was to assess the prevalence of gastrointestinal symptoms associated with SARS-CoV-2 infection and examine gastrointestinal-specific health outcomes in a quaternary referral hospital exclusively treating COVID-19 patients in São Paulo, Brazil ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies reported a significant decrease in endoscopy volume during the pandemic due to widespread stay-at-home orders. Moreover, due to overwhelmed healthcare systems, endoscopy units were utilized as COVID-19 units [ 25 ], with consequent widespread delays and an increasing backlog of elective cases [ 26 ]. These changes forced providers to communicate with patients via telemedicine route.…”
Section: Role Of Telemedicine In Gastroenterology During Covid-19mentioning
confidence: 99%
“…In addition to patient and other healthcare stakeholder education surrounding the facilitation of routine vaccinations, the use of telemedicine and remote diagnosis using medical imagery was also identified in the literature [ 15 , 22 , 24 ]. While some obstetrical care was directly related to diagnostic and similar imaging procedures, facilitation of this service line was also enhanced through the increased use of telehealth resources, as well as facility upgrades to enable safe patient throughput, adequate PPE, and additional medical supplies [ 9 , 38 ].…”
Section: Discussionmentioning
confidence: 99%